Familial idiopathic small-bowel and colonic varices in three siblings - Boland, Paul; Leonard, Jennifer; Saunders, Michael; Bursey, Ford (Endoscopy, 2014)
Idiopathic small-bowel and colonic varices are a rare source of bleeding from the gastrointestinal tract. To date there are only eight published case series of familial idiopathic small-bowel and colonic varices. We present a case series detailing three affected siblings who presented with significant lower gastrointestinal bleeding and had multiple varices on endoscopy and imaging. Though not confirmed, consanguinity in the parents suggests an autosomal recessive mode of inheritance. We summarize the literature to date and describe our institution’s experience of endoscopy, diagnostic imaging, and treatment in these patients.